Percutaneous left atrial appendage closure using the LAmbre device in patients with atrial fibrillation and left atrial appendage thrombus - Jin, Lu-Shen; Ke, Jin-Yan; Lin, Yuan-Nan; Li, Ling; Fu, Jia-Yang; Chen, Yi-Lian; Qiu, Yi-Xuan; Li, Xiao-Wei; Pan, Yang-Qi; Li, Yue-Chun (Frontiers in Cardiovascular Medicine, 2022)
Background: Left atrial appendage closure (LAAC) is considered a valid alternative for the prevention of thromboembolic stroke in patients with persistent left atrial appendage thrombus (LAAT) despite adequate anticoagulation. However, the data on LAAC using the LAmbre device for patients with LAAT is limited. This study was performed to explore efficacy and safety as well as to share the experience of the modified LAAC procedure with the LAmbre device. Methods: A total of 7 patients with persistent LAAT despite adequate anticoagulation underwent modified LAAC with the LAmbre device between November 2019 and April 2022. Transesophageal echocardiography was performed 3 months postoperatively to detect device-related thrombosis and peridevice leak. The patients’ clinical events were evaluated during the perioperative and follow-up periods. Results: The median age, CHA2DS2-VASc score, and HAS-BLED score of all patients were 71 [53-73], 3 [2-4], and 2 [2-3], respectively. In the procedure, a cerebral protection system was used in two patients. LAAC with the LAmbre device was successfully performed in all patients without perioperative events. During the median follow-up of 383 [325-865] days, postoperative transesophageal echocardiography was performed in six (85.7%) patients. Device-related thrombosis was detected in one (16.7%) patient, and no significant peridevice leak was observed. No thromboembolic event or bleeding event occurred in any patients. Conclusion: LAAC with the LAmbre device is effective and safe when performed by experienced operators in highly selected patients with LAAT after adequate anticoagulation.